THE EFFECT OF BOND CHARACTERISTICS, FINANCIAL PERFORMANCE AND MACRO VARIABLES ON RETURN OF CORPORATE BOND IN THE AGRIBUSINESS SECTOR - Kusumaningrum, Dewi; Anggraeni, Lukytawati; Andati, Trias (Jurnal Manajemen dan Agribisnis, 2019)
There are several reasons why companies choose to issue bonds rather than borrowing from banks. Interest paid by companies to bond investors is often lower than the interest rate charged by the bank, but still at least bond issuance from the agricultural sub-sector and chooses to lend to the bank. The purpose of this study is to analyze the influence of bond characteristics, financial performance and macroeconomic return on corporate bonds in the agribusiness sector. This study uses a panel data regression method consisting of 12 bonds with the vulnerable time between 2014-2015 \quarterly. Based on the panel data model shows that the characteristics of bonds (yield to maturity, coupon, rank, and duration), financial performance (CFOS) and macroeconomics (IHSG) have a significant effect on the return of bonds. The Company should consider the amount of bond yield and coupon to be issued and pay attention to financial performance, especially cash flow and capital expenditure (capital expenditure).Keywords: agribusiness sector, bonds, characteristics, performance, macroeconomics